A Review on Stem Cells: A New Toll in Diseases Therapy - Baseer, Abdul Qadeer; Mushfiq, Shafiqullah; Omid, Mohammad Tahir (Journal for Research in Applied Sciences and Biotechnology, 2023)
Stem cells are known as special somatic cell types that have the ability to self-renew and differentiate into various types of cells. They are categorized into two major groups such as embryonic stem cells and adult stem cells. Embryonic stem cells are pluripotent, which have the potency to differentiate into almost all cell types and grow up from the mesoderm, endoderm, and ectoderm germ layers at the beginning stages of embryo. While adult stem cells can be pluripotent or multipotent, which can differentiate into the family of a closely related cells. Over few decades, researchers have been studying and exploring new ways to treat different types of diseases like Parkinson’s and Alzheimer’s disease by using stem cells. Hence, embryonic and adult stem cells have been widely used in stem cell therapy. Here, we elaborate the problems of using embryonic stem cells and adult stem cells in stem cell therapy and its possible solutions, and discuss the applications of both stem cells types in biology-based field including disease modelling, regenerative medicine, drug discovery and cytotoxicity studies.